Pengaruh Karakteristik Organisasi, Kesesuaian Kompensasi, Sistem Pengendalian Internal dan Budaya Etis terhadap Fraud Pengadaan Barang/Jasa - Fithriani, Nurlaili; Pituringsih, Endar; Firmansyah, M (E-Jurnal Akuntansi; Vol 30 No 7 (2020)DO - 10.24843/EJA.2020.v30.i07.p17, 2020)
The purpose of this study is to examine whether the TPK characteristic variables, the suitability of compensation, internal control systems, and ethical culture have an influence on fraud procurement of goods / services. The study was conducted at the Village Government Agency in Central Lombok Regency. This research uses a quantitative approach using primary data collected by survey method through sending questionnaires to respondents. The sampling technique used was Claster Random Sampling, so that 195 people were obtained in 65 villages in Central Lombok Regency. The results showed that the characteristics of the Activity Management Team (TPK) and ethical culture had a significant negative effect on goods / services procurement fraud, compensation suitability had a significant positive effect on goods / services procurement fraud, while the internal control system had no effect on goods / services procurement fraud. Keywords: Organizational Characteristics; Suitability of compensation Internal Control System; Ethical Culture; Goods / Services Procurement Fraud.